Progressive Myoclonus Epilepsy in Congenital Generalized Lipodystrophy type 2: Report of 3 cases and literature review. (November 2016) - Opri, Roberta; Fabrizi, Gian Maria; Cantalupo, Gaetano; Ferrarini, Moreno; Simonati, Alessandro; Dalla Bernardina, Bernardo; Darra, Francesca
Highlights: PMEs may occur in Congenital Generalized Lipodystrophy type 2. PMEs may be related to selected mutations in BSCL2 gene. Early seizure onset in CGL2 patients may predict a precociously fatal course. PAS+ osmiophilic material accumulates in fibrocytes of CGL2-PME patients. Abstract: Purpose: A small case series with a neurodegenerative disorder involving central nervous system and related to Seipin mutations was recently reported. Herein we describe clinical and EEG features of three patients presenting with Progressive Myoclonus Epilepsy (PME) and Congenital Generalized Lipodystrophy type 2 (CGL2) related to novel Seipin mutations. Methods: The EEG-clinical picture was evaluated at epilepsy onset and in the follow-up period. The molecular analysis of BSCL2, Laforin and Malin genes was performed to patients and/or their parents by Denaturing High Performance Liquid Chromatography and automated nucleotide sequencing. Skin specimens collected from a patient were processed for histochemical and ultrastructural analysis. Results: The CGL2-PME syndrome co-segregated with two different BSCL2 genotypes: the homozygosity for c.782_783dupG involving exon 8 (two cases), or the compound heterozygosity for c.782_783dupG/c.828_829delAA (one case). Periodic-Acid Schiff positive osmiophilic material in the cytoplasm of fibrocytes and eccrine-gland cells were found in skin specimens. The lack of Lafora's bodies in skin specimens and the molecular analysis excluding mutations in Laforin and Malin genes ruled out Lafora disease. Conclusion: The spectrum of CGL2 associated to BSCL2 gene mutations may include PMEs. Selected mutations in BSCL2 gene seem to be related to PMEs in patients with CGL2 phenotype.